PENGARUH KETERSEDIAAN SARANA DAN PRASARANA TERHADAP KEPUASAN BELAJAR WARGA BELAJAR PADA PROGRAM KESETERAAN PAKET C DI PKBM NURUL ISLAM KARAWANG - Azizah Ismail, Neng Hikmah; Suminar, Uum; Meilya, Ika Rizqi (IKIP Siliwangi, 2025)
The availability of adequate educational facilities and infrastructure plays an important role in supporting an effective and comfortable learning process. This study aims to examine the influence of facility and infrastructure availability on the learning satisfaction of Package C students at PKBM Nurul Islam Karawang. The research employs a quantitative descriptive approach with simple random sampling. The population consisted of 102 students from grades X, XI, and XII, with a sample size of 51 determined by the Slovin formula. Data were collected using questionnaires and analyzed with simple linear regression. The results showed a t-value of 6.455 and a significance level of 0.000 (< 0.05), indicating a significant effect of facility and infrastructure availability on learning satisfaction. The coefficient of determination (R²) was 0.54, meaning that 54% of the variation in learning satisfaction is explained by the availability of facilities and infrastructure. This study highlights the importance of quality facilities and infrastructure in nonformal education.